Actualization of Sustainable Economic Development an Investment Strategy and Development of Indonesian Muslim Communities in The Digital Era - Ana Chonitsa; Adinda Riski Amalia; Abdul Aziz; Muhammad Mufid (Proceedings of Femfest International Conference on Economics, Management, and Business, 2023)
The actualization of sustainable economic development is a strategy to develop Indonesian Muslim communities in the digital era. This strategy uses the integration of two concepts, namely investment in financial education with the development of a Muslim personality throughout life. These two concepts work together to develop the economy in Indonesia. Through the formation of financial education and the formation of a Muslim personality that originates from the Al-Qur'an or Hadith. This strategy focuses on answering problems in economic progress that have an impact on human personality, namely competition between individuals, the attitude of justifying any means for personal gain, taking other people's rights and so on that harms others. Through this strategy it has a positive impact, namely creating a Muslim society that is responsive to economic changes, a Muslim society that is Rahmatan Lil 'alamin, a Muslim community with a moderate social spirit, and a Muslim community that loves Indonesia's homeland. Thus, this strategy is a way to actualize sustainable economic development in the digital era without abandoning the values of Islamic teachings.